Determinacion de afidos vectores del virus de la mancha anular de la fruta bomba (carica papaya L.) - Hernandez Perez, R.=700 1 Rodriguez Martin, E.F.
(En, Es)
ilus., 3 ref.
Keywords: CARICA PAPAYA; VIROSIS; APHIDOIDEA; VECTORES; VIRUS; MYZUS PERSICAE; APHIS GáYPII; CUBA